Realistic Reflections and Refractions on Graphics Hardware With Hybrid Rendering and Layered Environment Maps - Hakura, Ziyad S.; Snyder, John (Proceedings of the 12th Eurographics Workshop on Rendering Techniques, 2001)
We introduce hybrid rendering, a scheme that dynamically ray traces the local geometry of reflective and refractive objects, but approximates more distant geometry by hardware-supported environment maps (EMs). To limit computation, we use a greedy ray path shading model that prunes the binary ray tree generated by refractive objects to form just two ray paths. We also restrict ray queries to triangle vertices, but perform adaptive tessellation to shoot additional rays where neighboring ray paths differ sufficiently. By using layered, parameterized EMs that are inferred over a set of viewpoint samples to match ray traced imagery, we accurately handle parallax and view-dependent shading in the environment. We increase robustness of EMs by inferring them simultaneously across multiple viewpoints and including environmental geometry that is occluded from the viewpoint sample but is revealed in nearby viewpoints. We demonstrate realistic shiny and glass objects with a user-controlled viewpoint. https://youtu.be/2yP1Qhwo7Aw https://youtu.be/JJReuv5PA7Y https://youtu.be/4QsMo6En_7g https://youtu.be/xbCCeBngKRc https://youtu.be/7LvuKu_q47E https://youtu.be/VnFqGbg63RA https://youtu.be/BWHLoz8lGuw https://youtu.be/DlnDMX8eOyQ https://youtu.be/4AwcDLH8M8s